ANALISIS KOMPARATIF TINGKAT KESEHATAN PERBANKAN DENGAN METODE CAMELS DI ASEAN (Studi pada Bank Umum Indonesia, Malaysia, Singapura, Thailand, dan Filipina Tahun 2012-2016) - WIDYAWATI, WIWIK; MUSDHOLIFAH, (Jurnal Ilmu Manajemen (JIM), 2018)
This study aims to determine differences between Indonesian banking soundness with four other ASEAN countries namely Malaysia, Singapore, Thailand, and the Philippines using CAMELS indicator. Type of this research is explanatory research with quantitative approach. The research sample is three largest banks assets in each country. The data used in the form of annual reports are published on the official website of each bank. The data analysis technique used is based on the data distribution tested using Kolmogorov-Smirnov Test. Hypothesis testing using One-Way ANOVA and Kruskall-Wallis test. The result of statistical test shows that all indicators of financial ratios between Indonesian, Malaysian, Singaporean, Thailand and Philippines banks are significantly different. Overall, based on the CAMELS method approach, it can be concluded that Indonesian banking is better compared to other four ASEAN countries when viewed based on capital, asset quality and earnings indicators. Based on the indicators of management quality Singaporean banking are better than the banking four other ASEAN countries. Meanwhile, Thailand banking is better than the four other ASEAN countries seen by liquidity and sensitivity to market risk indicators. Keywords: ASEAN Banking Soundness, CAMELS, ANOVA, Kruskal-Wallis